Detection of nitrous oxide using infrared optical plasmonics coupled with carbon nanotubes. Issue 10 (21st September 2020) - Allsop, Thomas; Al Araimi, Mohammed; Neal, Ron; Wang, Changle; Culverhouse, Phil; Ania-Castañón, Juan D.; Webb, David J.; Davey, Paul; Gilbert, James M.; Rozhin, Alex
Abstract : Interest in gas sensing using functionalised carbon nanotubes is a major area of research that up until now have utilised their electrical properties, here the optical properties are exploited and used to detect a specific gas. Abstract : Interest in gas sensing using functionalised carbon nanotubes is a major area of research that utilises changes in their electrical properties induced by the reaction with a specific gas. This paper describes specific gas sensing on an optical platform consisting of a 2-dimensional nano-structured plasmonic array of nano-antennae/nanowires, with topological dimensions of mean radius of 130 nm, typical length of 20 μm and a period of 500 nm. The array is created by the spatial compaction of germanium oxides when the material interacts with ultra-violet irradiance, it can support infra-red localised surface plasmons. Carbon nanotubes are deposited upon the surface of the plasmonic platform followed by the application of the polyethyleneimine polymer. The resulting nanomaterials-photonic platform gives rise to the selective response to nitrous oxide gases, which are a major contributor to atmospheric degradation. We achieve the device sensitivity up to 100% atmosphere of nitrous oxide with a detection limit of 109 ppm, a maxiumum response time of nineteen seconds and yielding a full-scale deflection of +5.7 nm. This work demonstrates that the optical properties of specific carbon nanotubes can be used in a wide range of sensing applications offering a new sensing paradigm.